2013
DOI: 10.1007/s10964-013-9923-7
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Adolescent and Family Influences on Intimate Partner Psychological Violence During Emerging Adulthood and Adulthood

Abstract: The intergenerational transmission of violence directed toward intimate partners has been documented for the past three decades. Overall, the literature shows that violence in the family of origin leads to violence in the family of destination. However, this predominately cross–sectional or retrospective literature is limited by self–selection, endogeneity, and reporter biases as it has not been able to assess how individual and family behaviors simultaneously experienced during adolescence influence intimate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
56
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 115 publications
(147 reference statements)
8
56
0
4
Order By: Relevance
“…Two studies 191,192 reported useable data on the relationship between childhood behavioural problems and the victimisation and perpetration of domestic violence. Fergusson et al 191 estimated unstandardised regression coefficients of 0.05 (SE 0.01) and 0.03 (SE 0.01) for the association between conduct problems (age 7-13 years) and victimisation and perpetration, respectively, of intimate partner violence at 25 years of age.…”
Section: Extrapolating Childhood Outcomes Into Adult Outcomes: Analysmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies 191,192 reported useable data on the relationship between childhood behavioural problems and the victimisation and perpetration of domestic violence. Fergusson et al 191 estimated unstandardised regression coefficients of 0.05 (SE 0.01) and 0.03 (SE 0.01) for the association between conduct problems (age 7-13 years) and victimisation and perpetration, respectively, of intimate partner violence at 25 years of age.…”
Section: Extrapolating Childhood Outcomes Into Adult Outcomes: Analysmentioning
confidence: 99%
“…Lohman et al 192 provided estimates from a structural equation model, which included antisocial behaviour in adolescence as a predictor of intimate partner psychological violence in early and later adulthood. Although the parameter estimates for antisocial behaviour in adolescence were not statistically significant, parameter estimates were reported and are given here.…”
Section: Extrapolating Childhood Outcomes Into Adult Outcomes: Analysmentioning
confidence: 99%
“…For example, family stress has previously been shown to be associated with IPV, whether the family stress comes from poverty [59,60], negative emotionality [12], pregnancy [61,62], depression [62], alcohol or substance abuse [62,60] psychopathy [63], criminality [64], job stress [65,66] and low marital satisfaction [63,67,68]. The present findings extend previously published studies of IPV with concurrent family stress to include the observation that family stress can be predictive of later IPV, two years after the family stress was assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Family stress elicits violence ranging from verbal assault, to shoving a partner, to the use of a lethal weapon [11]. Family stress may come from marital discord [12], caregiver depression [13,14], substance abuse in the household [15,16], low economic resources [17], minimal social support [18] and occupational difficulties [19,20]. Research suggests lack of social support, low socio-economic indicators, and educational levels impact relationship distress [21], as well as IPV prevalence [22].…”
Section: Instrumentsmentioning
confidence: 99%
“…Indeed, research over the past two decades has consistently shown that women tend to be more likely than men to use this tactic in conflict with significant others, increasing the likelihood of male victimization (Harned, 2001;Hines & Saudino, 2003;Lohman, Neppl, Senia, & Schofield, 2013;Schnurr et al, 2013;Stockdale, Tackett, & Coyne, 2013). Recent studies have consistently shown that women use psychological aggression more than any other aggressive tactic in their intimate relationships (Dowd, Leisring & Rosenbaum, 2005;Harned, 2001;Straus & Sweet, 1992), with as many as 86% of heterosexual college women have reported perpetrating psychological aggression in their intimate relationships on at least one occasion (Hines & Saudino, 2003).…”
Section: Introductionmentioning
confidence: 99%